2009
DOI: 10.1111/j.1439-0531.2009.01508.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloprostenol in Equine Reproductive Practice: Something More Than a Luteolytic Drug

Abstract: Prostaglandin F(2α) and its analogues (PGF) are widely used in equine reproductive practice. The interval from PGF treatment to ovulation (ITO) varies greatly with a range from 2 to 16 days. Clinical observation suggests that mares mated and ovulated soon after PGF treatment may have poor fertility. Reproductive records of 329 cyclic Thoroughbred mares were analysed retrospectively. The following parameters were analysed: (i) use of cloprostenol; (ii) ITO and (iii) number of ovulations per cycle. According to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
9
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 13 publications
12
9
0
2
Order By: Relevance
“…Furthermore, the second hypothesis was also accepted: this correlation was significant in both PGF-induced and spontaneous estrous periods. Similarly, the ITO length was also positively correlated with PR, which is in agreement with previous reports [9,10,14]. As seems logical, the ITO had a fairly good correlation with the duration of the follicular phase with estrus-like echotexture.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the second hypothesis was also accepted: this correlation was significant in both PGF-induced and spontaneous estrous periods. Similarly, the ITO length was also positively correlated with PR, which is in agreement with previous reports [9,10,14]. As seems logical, the ITO had a fairly good correlation with the duration of the follicular phase with estrus-like echotexture.…”
Section: Discussionsupporting
confidence: 89%
“…The interval from PGF treatment to ovulation (ITO) is also greatly variable, ranging from 2 to 16 days [8][9][10], regardless of the day of the estrous cycle on which treatment is administered [7]. Several reports have analyzed the effect of PGF treatment to induce estrus on pregnancy rates (PRs), and although the overall PR of mares after PGF-induced cycles was not different to that of spontaneous cycles [9][10][11][12][13], when the PR of PGF-induced cycles were analyzed according to the ITO, it was observed that the PR increased as the ITO became longer [9,10,14]. It is likely that the ITO correlates well with the period in which the mare shows estrus-like echotexture.…”
Section: Introductionmentioning
confidence: 99%
“…As the IOI was shorter, the ERR was reduced. A similar relationship has been reported in Thoroughbred mares (Cuervo-Arango and Newcombe, 2010). In the latter study, the interval from PGF treatment to ovulation also influenced the pregnancy outcome of the mating of the subsequent estrus.…”
Section: Discussionsupporting
confidence: 70%
“…Since PGF shortens the IOI (Ginther, 1992) the Day of embryo flushing is likely to influence the subsequent IOI. Furthermore, evidence shows that the interval from PGF treatment to ovulation may influence the pregnancy rate (PR) (CuervoArango and Newcombe, 2010). However, the relationship between the IOI and the subsequent embryo recovery rate (ERR) has not been investigated in donor mares during an EET programs.…”
Section: Introductionmentioning
confidence: 96%
“…Several studies have shown a positive correlation between the length of the follicular phase and likelihood of establishing pregnancy in mares following PGF-induced [4,7,8] or spontaneous luteolysis [7]. Several studies have shown a positive correlation between the length of the follicular phase and likelihood of establishing pregnancy in mares following PGF-induced [4,7,8] or spontaneous luteolysis [7].…”
Section: Introductionmentioning
confidence: 99%